Analytical approach to stochastic assessment for balanced voltage sags and duration on transmission networks - Gopi R.J. (2023)
Stochastic assessment is a method to predict the severity, duration and number of voltage sags at a bus of interest in the transmission network. In this paper, a technique using impedance matrix for stochastic assessment was developed to predict the voltage magnitudes and duration due to faults at any bus in the electrical network. To illustrate the application and reliability of the proposed technique, the impedance matrix was applied to simple electrical network. The results conclusively point to the fact that the impedance matrix method is able to compute the predicted voltage magnitude at any bus, duration of sag and the number of sags per year. 2009 IEEE.